Insurance for Catastrophes - Indemnity vs. Parametric Insurance with Imperfect Information - Eberhard Feess; Cathrin Jordan; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2022)
Insurance for natural hazards - earthquakes, hurricanes, or pandemics - is rarely comprehensively adopted without intense government intervention, and even then it is often only a minority of properties or businesses that are insured. Efforts to close this insurance gap include the introduction of parametric (index) insurance products for various catastrophic risks. We compare parametric to indemnity insurance in a simple model where the insurance company has superior information about the probability of the event (reversed asymmetric information). We find that indemnity insurance tends to be welfare superior, because the coverage provided to agents who underestimate the event probability is larger than with parametric cover. Since it could plausibly be argued that a majority of the population is underestimating the risks of many types of extreme events, this difference in social welfare is potentially substantial.
Keywords: D81; D82; G22; 330; business interruption insurance; insurance for pandemics; parametric vs. indemnity insurance; reversed asymmetric information